Human cytomegalovirus infections in solid organ transplant recipients: an updated review / Mohd Fahmi Mastuki ... [et al.] - Mastuki, Mohd Fahmi; Mohd Taib, Niazlin; Masri, Siti Norbaya; Mohd Lila, Mohd Azmi; Camalxaman, Siti Nazrina (Faculty of Health Sciences, Universiti Teknologi MARA, 2022)
Human cytomegalovirus (HCMV) is an important cause of morbidity and mortality in immunocompromised individuals such as transplant recipients and paediatric patients. The approach to defining clinical syndromes related to the virus, diagnostic techniques, treatment, and prevention strategies have developed over time. This article provides an updated overview of the epidemiology, clinical outcomes, diagnosis, treatment, and prevention of HCMV disease in solid organ transplant (SOT) recipients.